PENGARUH LEVERAGE, KOMPENSASI RUGI FISKAL, UKURAN PERUSAHAAN, DAN KEPEMILIKAN KELUARGA TERHADAP TAX AVOIDANCE - Novita Saulina Br Situmorang; Vince Ratnawati; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
axes are the main source of state revenues that are capable of sustaining the needs of the state. The existence of different interests between the Taxpayer and the Government, tends to make the Taxpayer seek to reduce the amount of tax payments, both legally and illegally. This is possible if there are opportunities that can be utilized both because of the weakness of tax regulations and human resources (fiscus). This study discusses the effect of leverage, fiscal loss compensation, firm size, and family ownership on tax avoidance described in the company's annual report on mining sector in the period 2014-2016. The number of samples in this study as many as 18 companies, and sampling method is purposive sampling. The data analysis technique used is multiple regression analysis using SPSS 21 software. The results of this study indicate that leverage, fiscal loss compensation, firm size, and family ownership simultaneously have a positive effect on tax avoidance with a significance of 0.000. However, partially, leverage (sig 0.218), firm size (sig 0.097), and family ownership (0.103) have no effect on tax avoidance. Meanwhile, fiscal loss compensation negatively affects tax avoidance with 0.000 significance.Keywords : leverage, fiscal loss compensation, firm size, family ownership, tax avoidance.